ESTACIONALIDAD REPRODUCTIVA EN PERRAS PASTOR ALEMÁN DE PEDIGRÍ EN LIMA METROPOLITANA - Choy V., José Manuel (2005)
A study was done comparing the frecuency of estrus ocurrence in German Shepherd dogs in Lima, during the period 1997-2000. Data was obtained from the Peruvian German Shepherd Breeders Association, and from the local weather intitute (SENHAMI). The multiple lineal regresion was applied for datav analysis. A positive and significative relationship (p<0.05) between photoperiod, temperature, and month with the number of bitches in heat was found.